Peranan Penyuluh Pertanian Lapangan (PPL) sebagai Fasilitator Usahatani Petani di Subak Empas Buahan Kecamatan Tabanan Kabupaten Tabanan - NI PUTU ISTRI PADMASWARI; NYOMAN SUTJIPTA; I GEDE SETIAWAN ADI PUTRA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
The Role of Agricultural Field Extension (PPL) as a Facilitator of Farmers Farming in Subak Empas Buahan Tabanan Subdistrict, Tabanan Regency Agricultural extension workers are people who work in extension activities by communicating on target extension, so that the target was able to make the decision-making process correctly.Extension activities in agricultural development act as a bridge between the theory to practice run by the farmers with the aim of adding education and innovation of new farmers to a better and advanced agriculture. The purpose of this study is to know how the role of agricultural field extension (PPL) as a facilitator farmers farming in Subak Empas Buahan, District Tabanan.The results of the study showed that the role of extension (PPL) in facilitating the needs of farmers as educators, mediators, motivators, an evaluators. Based on the overall results of respondent’s responses the role of extension workers as educators obtained average score achievement of 3,94 are categorized good. Result of mediator role answer that is with average score 3,99with good category. Result of motivator role answer that is with achievement of average score obtained that is 4,10 with good category. Obtained the result of answers from the role of the evaluator is with the achievement of an average score of 3,92 with good category.